The Bella Vista - Cano, Alicia (Germany, 2012)
On the outskirts of a small provincial city in Uruguay, the Bella Vista Football Club lost its final game and was eliminated from its category; a fight broke out between the fans and players and the club was disbanded. The club house, empty for some time, was taken over by a well-known madam, who quickly turned it into a brothel for transvestites. Local residents, some frightened, others fed up, brought this to the attention of Patón Lerena, former director of the club, patriarch of a large family and local strongman. He immediately gathered a group together to evict the “undesirable” elements from the club. The local residents established a Catholic chapel there: the Jesus of Mercy Oratory. Since then, guided by a cheerful nun, the children attend catechism classes and dance and sing their praises to the Lord in the rooms that formerly housed the brothel. The transvestites were forced back into street prostitution. A madam and two transvestites, a macho-man and a devout old lady, will bring to life this battle for control of a single physical space.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films